Cost/Benefit Analysis of Managing Invasive Annual Grasses in Partially Invaded Sagebrush Steppe Ecosystems. Issue 1 (March 2014) - Sheley, Roger; Sheley, Jordan; Smith, Brenda
Abstract : Our objective was to evaluate the cost/benefit of a single herbicide application or targeted grazing of invasive annual grasses during restoration of partially invaded sagebrush steppe ecosystems used for livestock production. The cost/benefit model used is based on estimating the production of vegetation in response to implementing management and modeling cost/benefit economics associated with that prediction. The after-tax present value of added animal unit months (AUMs) obtained was lower than the present value of after-tax treatment costs after 20 yr for a single herbicide treatment, but higher than the present value of after-tax treatment costs for the grazing management scenario. Even at the highest weed utilization level, the value of added AUMs did not offset the cost of the treatment after 20 yr. However, the grazing treatment resulted in a value of added AUMs higher than the costs after 20 yr. Depending on the invasive weed utilization level, break-even points with targeted grazing occurred at anywhere from the first year to 7 yr. This assessment clearly shows that grazing management can be economically viable for managing annual grass-infested rangeland. In the future, models like the one used here can be improved by incorporating the rangeland management and restoration benefits on the wide variety of goods and services gained from rangeland.